Yolk-shell Si@void@C composite with Chito-oligosaccharide as a C–N precursor for high capacity anode in lithium-ion batteries. (May 2021) - Shao, Tan; Liu, Jian; Gan, Lihui; Gong, Zhengliang; Long, Minnan
Abstract: The yolk-shell structure of Si@void@C anode for lithium ion batteries with Chito-oligosaccharide (COS) as carbon and nitrogen source was successfully prepared by using a newly designed method. As a low-molecular-weight precursor, COS is completely soluble in an aqueous solution to make the composite more homogeneous. The COS derived carbon has a higher porosity than macromolecules derived carbon, providing reliable channels for ions to shuttle. In addition, amino groups from COS effectually promote the wettability of electrode interface. For the yolk-shell structure of Si@void@C composite, the outer carbon shell is not only conducive to the rapid transmission of electrons and lithium ions, but also to the reduction of charge transfer resistance and effective protection of the silicon core ball from electrolyte corrosion. Furthermore, the void layer between silicon core and carbon shell can adapt to huge volume expansion of Si and stabilize the electrode structure. Therefore, Si@void@C exhibits superior cycle stability and high rate performance. At a current density of 420 mA g −1, after 200 cycles, the Si@void@C maintains a high capacity of 1038.5 mAh g −1 . In this experiment, the innovative synthesis of a unique yolk-shell structure of Si@C composites is an effective way to obtain high-performance anode materials. Highlights: Chito-oligosaccharide is firstly introduced as carbon and nitrogen resources for preparing yolk-shell composite. The yolk-shell works well in preventing Si from direct contact with electrolyte and alleviating volume expansion. The composite has a higher porosity, providing reliable channels for ions to shuttle. The composite provides excellent conductivity and a buffer layer for volume expansion. The yolk-shell Si@void@C anode possesses high specific capacity and cycling stability.